Stopping Mass Atrocities: Targeting the Dictator - Weerdesteijn, Maartje (2015)
The international community has determined it carries the responsibility to protect civilians from atrocity crimes if a state is unable or unwilling to do so. These crimes are often perpetrated in authoritarian regimes where they are legitimized through an exclusionary ideology. A comparative case study of Pol Pot and Milosevic indicates that whether the leader truly believes in the ideology he puts forward or merely uses it instrumentally to manipulate the population, is an important variable, which affects the manner in which third parties can respond effectively to these crimes. While Pol Pot was motivated by his ideological zeal, Milosevic used ideology to create a climate in which mass atrocities could be perpetrated in order to garner further power and prestige. In Max Weber’s terminology, Milosevic was guided by instrumental rationality while Pol Pot acted on the basis of value rationality. This case study compares two crucial moments—Vietnam’s invasion of Cambodia and NATO’s bombing of Serbia when the crisis in Kosovo escalated—to analyze the responsiveness of the two leaders. It is argued that ideological leaders are less responsive than non-ideological leaders to foreign policy measures targeted to stop or mitigate the occurrence of atrocities.